2010
DOI: 10.1371/journal.pone.0011874
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Plasticity and Self-Fertilization in the Sea Anemone Aiptasia diaphana

Abstract: Traits that influence reproductive success and contribute to reproductive isolation in animal and plant populations are a central focus of evolutionary biology. In the present study we used an experimental approach to demonstrate the occurrence of environmental effects on sexual and asexual reproduction, and provide evidence for sexual plasticity and inter-clonal fertilization in laboratory-cultured lines of the sea anemone Aiptasia diaphana. We showed that in A. diaphana, both asexual reproduction by pedal la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…; Schlesinger et al. ). Although ~30% of individuals at Grassy Key Quarry (GKQ) in the Florida Keys shared a genotype with at least one other individual, the most common genotype was shared by only four anemones.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…; Schlesinger et al. ). Although ~30% of individuals at Grassy Key Quarry (GKQ) in the Florida Keys shared a genotype with at least one other individual, the most common genotype was shared by only four anemones.…”
Section: Discussionmentioning
confidence: 95%
“…; Grajales & Rodríguez , ), a genus in which individuals often form extensive monoclonal aggregations and are therefore considered pests in the aquarium trade (Schlesinger et al. ). However, individuals of B. annulata are much larger than those of Exaiptasia , and it has been suggested that large body size is linked to low clonal proliferation in some sea anemone species (Shick ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant reproductive mode in Aiptasia is pedal laceration, an asexual process that allows for rapid local proliferation and includes vertical symbiont transmission from parent to offspring (Muller‐Parker & Davy ; Schlesinger et al . ). Vectored introductions and clonal propagation through pedal laceration may explain the low genotypic diversity of S. minutum (clonality) observed in this study compared with previous work (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Carlon (1999) suggested that species with limited dispersal potential may have high rates of self‐fertilisation. Sexual reproduction between clone mates found in isolated environments, like in small canals inhabited by H. circumcincta , can occur if there are no barriers to self‐fertilisation (Schlesinger et al. 2010).…”
Section: Discussionmentioning
confidence: 99%